Metode Dan Corak Tafsîr Ayât Asykalat Karya Ibn Taimiyyah - Remer Muhamad; Syafruddin Syafruddin; Zulheldi Zulheldi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This Research aims to reveal the methods and Style of Tafsîr Ayât Asykalat book written by Ibn Taimiyah. What is the method of writing Tafsîr Ayât Asykalat book, what is the style of interpretation and what are the advantages and disadvantages of Tafsîr Ayât Asykalat. This study is Uses Library Research Methods with the primary data being Ibn Taimiyyah's book Tafsîr Ayât Asykalat written by Abdul Aziz Bin Muhammad al-Khalifah. Secondary data sources are in the form of scientific books of interpretation or other articles related to the problem being researched. After conducting the research it can be concluded that the method used by Ibn Taymiyyah is the method of muqaran, which is to compare one interpretation with another. Meanwhile, the style of Tafsîr Ayât Asykalat is the style of akidah, because almost the entire theme of the discussion of the verse has the nuances of akidah. The strength of the book Tafsîr Ayât Asykalat is that it provides broader insight into one theme of discussion, open the door to being tolerant by knowing the various interpretive views in one discussion, and proving that the Al-Qur’an is actually nothing contradictory. While the weakness of the methodology of this book of Tafsir is that it cannot be given to beginners because the discussion is too broad and sometimes uses scientific terms that are difficult for beginners to know, cannot be relied on to answer social problems in society because this interpretation is scientific and does not discuss interpretation to answer a reality that happened, the method of interpretation was not systematic, did not match the title of the book with the contents of the book, Ibn Taimiyyah did not issue a new opinion, only commented on the interpretation of friends or the history of salaf and khalaf scholars.